INVESTIGATING DISTORTION IN AUTOMOTIVE REAR ARMS: A FINITE ELEMENT ANALYSIS AND EXPERIMENTAL APPROACH - BIN KASIM, KHAIRULNIZAM (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
This project investigates the distortion of automotive parts subjected to a continuous virtual simulation process, from stamping to welding. The objective is to determine the optimal parameters for both the stamping and welding stages. In this sequential process, the properties derived from the stamping simulation are utilized in the welding simulation. The analysis was conducted using finite element software, Simufact.Forming 13.0 and Simufact.Welding 5.0, which are highly effective tools for simulating stamping and welding, offering fast and reliable results. To validate the simulation outcomes, an experimental study using an automated welding process was also performed. The automotive rear arm was selected as a case study, using materials SPH440 and STKM13A, which belong to the general steel category. This paper examines the distortion error percentage between the simulation and the actual welding process of the rear arm. The findings demonstrate that Virtual Manufacturing with Simufact.Welding 5.0 provides a solid understanding, as confirmed by experimental verification.